COVID-19 Lockdown and its Impact on Social–Ethics and Psycho-Social Support for Disability Care - Nwachukwu, P.T.T. (Journal of Intellectual Disability - Diagnosis and Treatment, 2021)
This paper aims to explore the social-ethics dimension and the psychosocial support for persons with disabilities, as well as health and social care practitioners during the COVID-19 pandemic and beyond regarding quarantine conditions currently ravaging the world. The COVID-19 outbreak has motivated the enactment of public health control procedures, particularly quarantines. The impacts of quarantines during this COVID-19 outbreak period and the interventions to relieve the strain are discussed through a descriptive analysis pattern and linked with social ethic and psychosocial support for behavioural health and social work practices. The role of the social-ethic perspective is that it is geared towards reducing the psychosocial impacts of the COVID-19 quarantine for persons with disabilities and for disability care. This paper outlines psychosocial uneasiness, including distress and stressors, as a result of the hazards and anxiety sensitivities, as well as the immense concern for persons with disabilities and their care practitioners during quarantine and beyond. This paper offers new insights on the COVID-19 virus and the quarantine measures that were missed, which could have averted its spread globally; quarantine or lockdown has a secondary effect in lessening the capacity of the virus's transmission and decreases the likelihood of people contracting, and thus infecting others. This paper suggests recommendations for persons with disabilities in quarantine and their families and the management of perceptions of public health risks, threats, and issues about health and social care workers becoming "covitors” (meaning COVID-19 survivors) now and post-COVID-19.